2022
DOI: 10.3389/fonc.2022.997235
|View full text |Cite
|
Sign up to set email alerts
|

ER stress as a trigger of UPR and ER-phagy in cancer growth and spread

Abstract: Tumors can survive environmental and metabolic stress by triggering homeostatic responses that re-establish the pre-stress status and permit them to grow and thrive. The endoplasmic reticulum (ER) is the organelle where proteins undergo post-translational modifications and are folded and exported to the secretory pathway. Its environment and activity are therefore fundamental for proteostasis, i.e., the plethora of mechanisms controlling protein formation, folding, degradation, and secretion, needed to assure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 87 publications
0
5
0
Order By: Relevance
“…The initiation of the UPR in tumor cells, especially when subjected to high levels of endoplasmic reticulum (ER) stress, plays an important survival strategy [23]. When these stress response mechanisms fail to fully correct the protein accumulation problem, the UPR further promotes tumor cells to initiate the process of autophagy, an intracellular recycling mechanism for degrading and recycling defective cellular components, including damaged organelles and protein aggregates [24][25][26]. This process not only helps to maintain the stability of the intracellular environment, but also reduces the risk of cell death due to accumulated damage.…”
Section: Discussionmentioning
confidence: 99%
“…The initiation of the UPR in tumor cells, especially when subjected to high levels of endoplasmic reticulum (ER) stress, plays an important survival strategy [23]. When these stress response mechanisms fail to fully correct the protein accumulation problem, the UPR further promotes tumor cells to initiate the process of autophagy, an intracellular recycling mechanism for degrading and recycling defective cellular components, including damaged organelles and protein aggregates [24][25][26]. This process not only helps to maintain the stability of the intracellular environment, but also reduces the risk of cell death due to accumulated damage.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that specific ER‐phagy receptors promote cancer cell survival and migration for certain cancers [104]. This has been most clearly documented with Sec62, CCPG1, and FAM134B.…”
Section: Cancersmentioning
confidence: 98%
“…Cancer has long been linked to increased ER stress, caused by both intrinsic and extrinsic factors. The uncontrolled proliferation of cancer cells drives increased protein translation and therefore more ER stress; this stress is exacerbated by a tumor microenvironment low in oxygen and nutrients and high in certain fatty acids and other metabolites [104]. This strong link between cancer and ER stress begs the question: what role do the major ER protein quality pathways—including the unfolded protein response (UPR), ER‐associated degradation (ERAD) and ER‐phagy—play in tumorigenesis and metastasis?…”
Section: Cancersmentioning
confidence: 99%
See 1 more Smart Citation
“…Alteration of ER protein folding capacity may cause an increased proportion of unfolded and misfolded proteins in ER lumen which triggers loss of ER homeostasis and proteostasis and generates a detrimental cellular environment [ 6 , 7 , 8 ]. Several molecular and biophysical mechanisms are triggered to reverse and restore ER homeostasis such as (1) ER-associated degradation (ERAD), which triggers the misfolded protein degradation from ER lumen; (2) Unfolded protein response (UPR) involving the restoration of ER proteostasis by activation of three transduction signalling –IRE1, ATF6 and PERK branch-; and (3) Reticulophagy, the process of ER remodelling by autophagy of membranes and associated proteins (see reviews [ 9 , 10 , 11 , 12 , 13 , 14 ]). Pathophysiological factors occurring in cardiovascular diseases (CVDs) such as metabolic derangement, hypoxia, hypertrophy or inflammation require an increased protein expression, thus enhancing the disruption of the cellular proteostasis [ 15 , 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%